2000
DOI: 10.1007/s004110000049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwaves (900 MHz) on the cochlear receptor: exposure systems and preliminary results

Abstract: The purpose of this paper is to present the experimental device and the work in progress performed in search for objective organic correlation of damage to hearing, examining possible acoustic otofunctional effects on the cochlear epithelium of the rat due to exposure to microwaves (900 MHz). Two experiments using male Sprague-Dawley rats were carried out with a far-field exposure in a cubic chamber. No statistically significant evidence was obtained at both specific absorption rate (SAR) values. The exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…They found that average TEOAE levels (averaged across a frequency range) changed less than 2.5 dB between pre-and post-, genuine and sham exposure and the authors concluded that a 10-min exposure of EMFs emitted from a mobile phone had no immediate after-effect on measurements of hearing thresholds and TEOAE in young human subjects. These results are also in agreement with the negative findings in animal studies [Marino et al, 2000;Kizilay et al, 2003;Aran et al, 2005;Galloni et al, 2005]. Thus, our study, consistent with previous research, has found no effect of mobile phone exposure on outer hair cell function or on vestibular function as assessed by the VOR in either subjects who had suffered from symptoms after mobile phone usage or symptom free controls, and no increased ability of the subjects to tell whether an exposure was true or sham.…”
Section: Discussionsupporting
confidence: 95%
“…They found that average TEOAE levels (averaged across a frequency range) changed less than 2.5 dB between pre-and post-, genuine and sham exposure and the authors concluded that a 10-min exposure of EMFs emitted from a mobile phone had no immediate after-effect on measurements of hearing thresholds and TEOAE in young human subjects. These results are also in agreement with the negative findings in animal studies [Marino et al, 2000;Kizilay et al, 2003;Aran et al, 2005;Galloni et al, 2005]. Thus, our study, consistent with previous research, has found no effect of mobile phone exposure on outer hair cell function or on vestibular function as assessed by the VOR in either subjects who had suffered from symptoms after mobile phone usage or symptom free controls, and no increased ability of the subjects to tell whether an exposure was true or sham.…”
Section: Discussionsupporting
confidence: 95%
“…Low-level noise exposure ͑Skellett et al, 1996͒, increased body temperature due to fever ͑O'Brien, 1994͒, administration of salicylate ͑McFadden andPlattsmier, 1984;Janssen et al, 2000;Parazzini et al, 2005a͒, or Some authors studied the interaction between mobile phone radiation and the cochlear OHCs functionality by means of OAEs both in animals and humans, observing sometimes significant effects that might be attributable to exposure, but these results are inconsistent and need further confirmation. Marino et al ͑2000͒ found no statistically significant evidence measuring DPOAEs in Sprague-Dawley rats after chronic exposure to EMFs. Kizilay et al ͑2003͒ measured DPOAEs in adult and developing rats after chronic exposure to EMFs from a mobile phone showing no hearing deterioration, at least at outer ear, middle ear, and cochlear levels.…”
Section: Introductionmentioning
confidence: 80%
“…Dealing with central auditory pathways, some authors (Kellenyi et al, 1999;Arai et al, 2003;Hamblin et al, 2004) have studied the interactions between mobile phones and the central auditory system, but their results appear contradictory, finding an effect only in individual cases even when the experimental condition were similar. Some other authors (Grisanti et al, 1998;Kizilay et al, 2003;Ozturan et al, 2002;Marino et al, 2000;Galloni et al, in press) studied the interaction between mobile phone radiation and the inner ear, in particular the cochlear outer hair cells (OHC). They measured otoacoustic emissions (OAE) both in humans and in animals, resulting sometimes in significant changes, but their results need further confirmation.…”
Section: Introductionmentioning
confidence: 98%